PELEMBAGAAN HUKUM PERDATA ISLAM DI INDONESIA MELALUI SCREENING BOARD PANCASILA - Imron, Ali (Kopertais Wilayah X Jawa Tengah, 2014)
AbstractCivil law of Islam in indonesia is expected to create well-being materil and residents immateril for all indonesian people not to disregard the interests of some group and other groups. Law in indonesia should conform to the customs local indonesia entering in pancasila values.This paper intends to know the meaning of pancasila as screening board in the development of law in indonesia , strategy and the use of civil law of islam in indonesia.Pancasila serves as a filter on various values or norms that comes from outside. Law making procces, law awareness and law enforcement procces in indonesia always use pancasila as screening board in the use of universal values to become the norm positive law in indonesia.The use of islamic civil law in indonesia can be done through two ways namely first through the transformation of the value of the substance of islamic civil law Â to the community cultural tradition of culture in indonesia that gradually long term will become customary law .The second, islamic civil law trying to become positive law indonesia through screening board pancasila.Keyword: Pancasila, Islamic civil law, development